2021
DOI: 10.1016/j.jare.2020.06.014
|View full text |Cite
|
Sign up to set email alerts
|

New biodegradable nanoparticles-in-nanofibers based membranes for guided periodontal tissue and bone regeneration with enhanced antibacterial activity

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 95 publications
(99 reference statements)
1
82
0
Order By: Relevance
“…Such a result might be due to TSNP stacking (as observed in SEM images), which reduced the mobility of the polymer chains. A similar outcome was also reported by Abdelaziz et al (2020) as a result of adding hydroxyapatite nanoparticles to PCL composites [54].…”
Section: Mechanical Propertiessupporting
confidence: 89%
“…Such a result might be due to TSNP stacking (as observed in SEM images), which reduced the mobility of the polymer chains. A similar outcome was also reported by Abdelaziz et al (2020) as a result of adding hydroxyapatite nanoparticles to PCL composites [54].…”
Section: Mechanical Propertiessupporting
confidence: 89%
“… [ 52 ] Silver nanoparticles Electrospinning nanofibrous with HA & silver nanoparticles N/A Initial material characteristics, release profile, and antimicrobial activity 32 days Improved bone regeneration activity; silver nanoparticles enhanced antibacterial effect. [ 47 ] Doxycycline & simvastatin Core-Shell poly-(D, l -Lactide- co -Glycolide)-chitosan Nanospheres IL-1β, MMP-8, VEGF Initial material characteristics, release profile, antibacterial examination, gene expression analysis, and in vivo periodontal healing evaluation 28 days Scaffold constantly released simvastatin and doxycycline and significantly inhibited P. gingivalis and S. sanguinis ; down-regulated IL-1β & MMP-8, up-regulated VEGF, and decreased bone loss in rat model. [ 50 ] nMgO Biodegradable multifunctional nanofibrous membrane N/A Initial material characteristics, antibacterial effects, osteogenesis evaluation, and in vivo periodontal healing evaluation 14 days in vitro ; 6 weeks in vivo nMgO incorporated membranes enhanced osteogenic property & the antibacterial effect against E. coli and S. aureus ; enhanced periodontal regeneration in rat model.…”
Section: Purpose Of Use Of Biomaterials Scaffolds For Periodontal Regementioning
confidence: 99%
“…Silver and magnesium (Mg) are another example of anti-microbial components. Abdelaziz et al reported that electrospun nanofibers containing silver nanoparticles had antibacterial effects over 32 days [ 47 ]. Liu et al reported that magnesium oxide (MgO)-conjugated nanofibrous membrane showed antibacterial activities to E. coli and S. aureus in a dose-dependent manner and showed promising in vivo efficacy in periodontal regeneration in rats [ 48 ].…”
Section: Purpose Of Use Of Biomaterials Scaffolds For Periodontal Regementioning
confidence: 99%
“…Biodegradable electrospun membranes of poly(caprolactone) (PCL) or polylactide/cellulose acetate (PLA/CA) embedded with nano-HAp and AgNPs promoted the formation of bone-like apatite. The nanofibrous composites exhibited prolonged bactericidal effects, being proposed as suitable materials for orthodontic applications [ 322 ]. Liu et al, reported the successful fabrication of nanofibrous materials based on PLA/HAp nanowires modified with polydopamine membrane and coated with polypyrrole-stabilized AgNPs.…”
Section: Silver Nanoparticles For Tissue Engineeringmentioning
confidence: 99%